1987
DOI: 10.1111/j.1365-2265.1987.tb00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Aspects of Pituitary Stalk Enlargment

Abstract: Four patients with various endocrine deficiencies of a predominantly hypothalamic nature are described, in whom computed topographic scans demonstrated pituitary stalk enlargement. In one, a disseminated papular skin eruption with regional pleomorphism and spontaneous regression appeared 4 years after the development of the initial symptoms of diabetes insipidus, and led to a diagnosis of xanthoma disseminatum, a rare type of histiocytosis. It is suggested that this patient's endocrine dysfunction is also due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Treatment of cutaneous and mucosal XD has been associated with varying degrees of success. Options including diet, 1,17 surgical excision, 1,4,7,9,18 electrocoagulation, 18 cryotherapy, 17 radiation, 1,5,19 glucocorticoids, 6,8,13,18,20,21 anti-metabolites, 5,20 anti-cancer drugs, 4,17,21,22 lipid lowering agents, 4,[23][24][25] or a combination of these therapies have been tried. 4,17,20,21 Some of these modalities have been used for intracranial lesions (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of cutaneous and mucosal XD has been associated with varying degrees of success. Options including diet, 1,17 surgical excision, 1,4,7,9,18 electrocoagulation, 18 cryotherapy, 17 radiation, 1,5,19 glucocorticoids, 6,8,13,18,20,21 anti-metabolites, 5,20 anti-cancer drugs, 4,17,21,22 lipid lowering agents, 4,[23][24][25] or a combination of these therapies have been tried. 4,17,20,21 Some of these modalities have been used for intracranial lesions (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…5 reported that skin eruptions appeared 4 years after the onset of diabetes insipidus in 1 / 4 patients with a thickened pituitary stalk. Diabetes insipidus occurs in about 40-50% of patients and can represent the first symptom of the disease.…”
mentioning
confidence: 99%
“…Puig et al . 5 reported that skin eruptions appeared 4 years after the onset of diabetes insipidus in 1 / 4 patients with a thickened pituitary stalk. And Mahnel et al .…”
mentioning
confidence: 99%